(untitled) (Research, Society and Development, 2020)
Objective: Conduct health education intervention with Community Health Agents (ACS) in the Family Health Units (USF) of the Distrito D’ÁGUA, in Belém-PA, about risk factors, prevention, signs and symptoms of skin cancer (CP). Methodology: It consisted of a questionnaire about basic knowledge concerning the CP was carried out, before and after the lecture, in order to measure the impact of the acquired information and subsequent discussion on the participants’ knowledge. After the lectures, informative folders on the topic were delivered and any doubts clarified. After the lectures, the questionnaire data were organized and analyzed with Excel 2013 software, using descriptive analyzes. Results: Among the 64 participants, the female gender predominated (76.6%) and the average age was 38 years, of which 57.8% declared themselves as light brown. Regarding the level of education, 54.2% completed high school, 23.4% completed higher education, 18.7% have incomplete higher education and 1.5% have not completed high school. Sunscreen lotion was used by 71.9% of the interviewed, umbrella by 65.2%, sunglasses by 31.2%, and hat / cap by 20.3%. After the discussion, there was an increase of 4% of correct answers about the relationship between sun and CP, and 15.7% regarding preventive measures for the disease. There was a general increase of 16% in the degree of knowledge about the disease, with an increase of 25% in the perception of signs and symptoms. Conclusion: A greater dominance of the CHA on the subject was noted, which can improve self-knowledge and consequently promote better guidance for the community.